SULAWESI SEBAGAI DAERAH TUJUAN MIGRASI BANGSA AUSTRONESIA (TINJAUAN BERDASARKAN DATA ARKEOLOGIS) - Nurani, Indah Asikin (Berkala Arkeologi, 1998)
The following will review some of the cultural data found in Sulawesi in connection with the search for the base area of the culture brought by the Austronesian people. This paper is intended to reveal the position of the root of this culture. In addition, the problem in this paper is how important is the Sulawesi region in the migration of the Austronesian people? and based on the migration theory, it will be asked whether the Sulawesi area is the area of origin or the destination of the migrants? These two questions will be tried to answer based on archaeological data.